2017
DOI: 10.18203/2394-6040.ijcmph20173842
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality at a tertiary care teaching hospital in Dibrugarh district, Assam: a retrospective study

Abstract: Background: Maternal mortality is a measure of quality of health care in a community. Assam has the highest maternal mortality rate among all India’s states, which is almost double the national average, with around 328 deaths per 100 000 live births. Three quarters of these deaths are among the tea plantations community. It has serious implications on the family, the society and the nation. Maternal mortality rate (MMR) is a very sensitive index that reflects the quality of reproductive care provided to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…In our study, 89.43% of maternal deaths were occurred in women belonging to rural areas which were very similar to results obtained by Shannon Fernandes et al where 78.6% deaths were from rural areas 9 . In this study 55% deaths were recorded in the tea tribe community but another study conducted in Dibrugarh shows a higher percentage of 66.7% 11 . In the present study 5 4.…”
Section: Discussioncontrasting
confidence: 49%
“…In our study, 89.43% of maternal deaths were occurred in women belonging to rural areas which were very similar to results obtained by Shannon Fernandes et al where 78.6% deaths were from rural areas 9 . In this study 55% deaths were recorded in the tea tribe community but another study conducted in Dibrugarh shows a higher percentage of 66.7% 11 . In the present study 5 4.…”
Section: Discussioncontrasting
confidence: 49%
“…In the study of Lima Hazarika et al the MD were maximum in the early age group of 15 to 20 years. 3,5 In the present study maternal deaths during post natal care period (PNC) cases were 48%. In the study of Surekha N. Khandale et al it was 53.84% and the study of Khumanthem Pratima Devi et al PNC cases were 70%.…”
Section: Discussionmentioning
confidence: 52%
“…It differs from region to region. 5,6 The causes of maternal mortality can be classified as direct, indirect and coincidental causes. 7 Direct causes are those that are directly related to obstetric complications due to pregnancy, labour or puerperium.…”
Section: Introductionmentioning
confidence: 99%
“…1) where there are structural social problems and migratory states due to forced displacement (rural to urban areas), increasing rates of violence, accidents, and injuries. Maternal deaths are multifactorial and in a large proportion preventable and associated in a large proportion with problems in the social structure, as was observed in the study by Hazarika L & Pukan P [1], where it was identified that follow-up was important for the prevention of maternal deaths of pregnancy at the community or institutional level, promoting prenatal visits, limiting the practices of irrational cultural beliefs, and reducing inequities.…”
Section: Resultsmentioning
confidence: 90%
“…Maternal mortality (MM) is a public health problem that mainly affects developing countries with a family, social and economic impact [1]. Official reports on the behavior of maternal mortality at the level of Cali and the Department of Valle del Cauca, report the behavior of the MM georeferenced by commune without having described the pattern of geographic distribution associated with economic variables and social determinants [2].…”
Section: Introductionmentioning
confidence: 99%